2007
DOI: 10.1111/j.1524-4725.2007.33000.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Primary Acral Melanomas in African-Americans: A Case Series and Review of the Literature

Abstract: Patients with multiple acral melanomas have not, to our knowledge, been reported thus far. It can be extrapolated from current literature, however, that appropriate management of these patients, including staging work and surgical intervention, is to be determined by the individual characteristics of the melanoma and the patient's concomitant risk factors, if any.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 84 publications
3
20
0
Order By: Relevance
“…A recent systematic review of the literature [2], and corroborated in a case-control study in our population [6], revealed that AM is more prevalent in individuals in the fifth to seventh decades of life [4]. Surprisingly, patients reported herein are under 40 years old.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…A recent systematic review of the literature [2], and corroborated in a case-control study in our population [6], revealed that AM is more prevalent in individuals in the fifth to seventh decades of life [4]. Surprisingly, patients reported herein are under 40 years old.…”
Section: Discussionmentioning
confidence: 71%
“…To the best of our knowledge, there is just one other report of multiple primary AM presented in 4 African-American patients [4], the 2 cases reported herein being the first series in Caucasians.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Numerous volar melanotic macules, so called acral melanosis, has been reported in association with primary acral melanomas. 5,11 Specific genetic defects are involved in the pathogenesis of melanotic macules as certain familial lentiginoses 56 can exhibit volar melanotic macules such as Peutz-Jegher syndrome, Leopard syndrome, and Carney syndrome (also known as Lentigines, Atrial myxomas, Mucocutaneous myxomas, and Blue nevi (LAMB) or Nevi, Atrial myxoma, Myxoid neurofibroma, and Endocrine disorders/Ephelides (NAME) syndrome). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In the familial setting, volar macules are acquired during childhood and found commonly on the fingers as opposed to idiopathic cases, which affect middle-aged and older adults and are found more commonly on the soles and palms.…”
Section: Discussionmentioning
confidence: 99%